Electrochemical Properties of the Oxo-Manganese-Phenanthroline Complex Immobilized on Ion-Exchange Polymeric Film and Its Application as Biomimetic Sensor for Sulfite Ions - Machini, Wesley B. S. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Wiley-Blackwell, 2014)
A biomimetic sensor containing the oxo-bridged dinuclear manganese-phenanthroline complex incorporated into a cation-exchange polymeric film deposited onto glassy carbon electrode for detection of sulfite was studied. Cyclic voltammetry at the modified electrode in universal buffer showed a two electron oxidation/reduction of the couple Mn-IV(mu-O)(2)Mn-IV/Mn-III(mu-O)(2)Mn-III. The sensor exhibited electrocatalytic property toward sulfite oxidation with a decrease of the overpotential of 450 mV compared with the glassy carbon electrode. A plot of the anodic current versus the sulfite concentration for potential fixed (+0.15 V vs. SCE) at the sensor was linear in the 4.99 x 10(-7) to 2.49 x 10(-6) mol L-1 concentration range and the concentration limit was 1.33 x 10(-7) mol L-1. The mediated mechanism was derived by Michaelis-Menten kinetics. The calculated kinetics values were Michaelis-Menten rate constant=K-M(app)=1.33 mu mol L-1, catalytic rate constant=6.06 x 10(-3) s(-1) and heterogeneous electro-chemical rate constant=3.61 x 10(-5) cm s(-1).
Keywords: Biomimetic oxo-manganese complex; Biomimetic activity; Electrocatalytic sulfite sensor